1996
DOI: 10.1021/es9602758
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of the Spatial Extent of Sediment Toxicity in Major U.S. Estuaries

Abstract: Acute laboratory toxicity tests were performed on surficial sediments collected from 1176 locations throughout 22 estuarine areas in the United States. Toxicity was determined with three standardized procedures:  10-day amphipod survival tests with solid-phase (bulk) sediments; 5-min microbial bioluminescence tests with organic solvent extracts of the sediments; and either 1-h sea urchin fertilization tests or 48-h mollusc embryo tests with the porewater of the sediments. Test results were weighted to the size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(97 citation statements)
references
References 17 publications
1
95
0
1
Order By: Relevance
“…This definition of toxicity has been used nationwide by both NOAA (Long et al 1996) and the United States Environmental Protection Agency (USEPA) (2006) and used throughout all of Puget Sound . Samples were defined as toxic in the HRGS assay if the mean response was significantly greater than the negative control and greater than the 90% upper prediction limit of 37.1 mg benzo[a]pyrene/g (i.e., mgB[a]p/g).…”
Section: Data Analysesmentioning
confidence: 99%
“…This definition of toxicity has been used nationwide by both NOAA (Long et al 1996) and the United States Environmental Protection Agency (USEPA) (2006) and used throughout all of Puget Sound . Samples were defined as toxic in the HRGS assay if the mean response was significantly greater than the negative control and greater than the 90% upper prediction limit of 37.1 mg benzo[a]pyrene/g (i.e., mgB[a]p/g).…”
Section: Data Analysesmentioning
confidence: 99%
“…Summers (2001) concluded that nearly 30% of the total US estuarine area displayed poorer than expected biological condition, based on sediment toxicity, benthic and fish community composition and fish pathology, while Long et al (1996) found that nearly 11% of the total area (277 km2 of 2532 krn2) of 22 major US estuaries exhibited significant acute toxicity to amphipods. Local waterbodies demonstrate similar patterns-for example, PSAMP (2002) concluded that 63% of the total area of Puget Sound was degraded, based on sediment chemistry, toxicity and benthic community structure.…”
Section: List Of Tables and Figuresmentioning
confidence: 99%
“…Carr et al (1996a) stated that porewater tests using sea urchins were considerably more sensitive than sediment amphipod testing, based on an evaluation of sediment toxicity in the vicinity of offshore oil & gas platforms. Long et al (1996) found that tests involving the effects of 100% porewater on sea urchin fertilization (Arbacia punctulata), or sea urchidabalone larval development (Strongylocentrotus purpuratus, Haliotis rufescens) led to the determination that 43% of the total area in major US estuaries was toxic, while tests involving the effects of whole sediment amphipod survival led to the determination that only 11% of the total area was toxic. Porewater toxicity testing, therefore, was considered more sensitive than amphipod toxicity testing on whole sediment.…”
Section: Sensitivity Of Porewater Toxicity Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…According to some surveys conducted in the United States, the quantities approach billions of metric tons of sediment representing potentially significant ecological and human health risks [4][5][6]. Furthermore, extensive surveys of these sediments have shown many to be toxic to benthic marine organisms [11,12]. Estimated costs associated with managing these sediments in terms of remediation (e.g., dredging and capping) and postoperational monitoring are in the billions of U.S. dollars [13].…”
Section: Introductionmentioning
confidence: 99%